FUNGSI PAGUYUBAN PONOROGO DALAM MELESTARIKAN KESENIAN REOG PONOROGO DI DESA ABADI JAYA KECAMATAN MAGINTI KABUPATEN MUNA - Siti Ummi Latifah; NAsruddin Suyuti; Ashmarita Ashmarita (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study aims to identify and to describe the activities carried out by the Ponorogo Paguyuban in an effort to preserve the art of Reog in the Abadi Jaya Village, Maginti District, West Muna District. This research uses structural functionalism theory. The method is the ethnographic method with collection data by using both observational techniques, in-depth interviews, and Purposive Sampling informant selection techniques. The results show that the activities carried out by the Ponorogo Paguyuban in an effort to preserve the Reog Ponorogo arts included training activities for Jathil dancers performed twice a week, monthly social gathering and hospitality activities. Whereas the function of the Ponorogo Circle of Friends is carried out in an effort to preserve the art of Reog in the form of internalizing Jathil dancers in the art of Reog ponorogo, embracing the younger generation in an effort to preserve the art of Reog and performing to introduce Reog ponorogo art to the general public. So that this study recommends for some parties, namely community members to collaborate with schools in Abadi Jaya Village to make Reog ponorogo art as one of the subjects of local content so that efforts to preserve Reog art can run optimally.